Geochemical peculiarities and genesis of metaandesites and metadacites of the Novogorovka greenstone structure (Ukrainian Shield) - Artemenko, G.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Metaandesites of tholeiitic series of parageneration KT-3 of metamorphosed komatiite-tholeiitic formation of Novogorovka GS can be formed as a result of the fractional crystallization of mafic magma from a plume source in the shallow magma chamber (<40 km). They have a low magnesium number (mg# = 0.32). Metadacite located among the rocks of the parageneration of KT-3 were formed in a different magmatic source and are likely more recent. They belong to the calc-alkaline series, are characterized by high magnesium number (mg# = 0.51) and strongly contaminated by a crustal material. Metadacite can be formed by mixing melts of the mafic and silicic compositions or by assimilation of host rocks by basites in a shallow magma chamber (<40 km).